Comparison of Reporting Quality in National Cystic Fibrosis Patient Registries: Implications for Identifying Use of Novel CFTR Modulators - Owen W. Tomlinson; Philip Mitchelmore; Craig A. Williams (Pulmonary Therapy)
Abstract Introduction Advances in development of cystic fibrosis transmembrane conductance regulator modulator (CFTRm) therapies mean that now people who are heterozygous (instead of having to be homozygous) for the common F508del variant can benefit from these therapies. Recent economic estimates suggest only approximately 15% of the global population have CFTRm access, yet it is unknown how prevalence of F508del and economic factors may affect this availability. Methods Data related to prevalence of cystic fibrosis (CF), CFTRm usage, and prevalence of F508del in 10 countries were extracted from publicly accessible registry reports from 2021. National gross domestic product (GDP) was obtained via open access World Bank data. Descriptive statistics and correlation coefficients assessed relationships. Results Notable discrepancies were noted in the equity of availability of data between national registries—only four countries reported number of patients eligible for CFTRm. Registry data represented 70,694 patients, with 42,858 found to be using CFTRm (60.6%). Prevalence of CFTRm usage ranged from 1.8% to 76.7% and prevalence of F508del ranged from 35.2% to 94.4%. The correlation between prevalence of CFTRm usage and F508del is positive (r = 0.56, p = 0.10), and the correlation between CFTRm usage and GDP (per capita) was also positive, and significant (r = 0.72, p = 0.02). Conclusion Both F508del prevalence and GDP are associated with variable CFTRm usage rates, although a predominant reason is unclear as a result of poor consistency in registry reporting. Urgent action is needed to create uniform reporting of registry data and increase availability of novel CFTRm therapies to the global CF population.